2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649620
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear forecasting measurement of magnetoencephalogram recordings from Alzheimer's disease patients

Abstract: Abstract-The goal of this study was to analyze the magnetoencephalogram (MEG) background activity in patients with Alzheimer's disease (AD) using a nonlinear forecasting measure. It is a nonparametric method to quantify the predictability of time series. Five minutes of recording were acquired with a 148-channel whole-head magnetometer in 15 patients with probable AD and 15 elderly control subjects. Stationary epochs of 5 seconds (848 points, sample frequency of 169.55 Hz) were selected. Our results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…It has been reported that progressive patients showed a differential profile of FC values compared with those patients who remained stable over time (Bajo et al, 2012 ). Time series was found more predictable for AD by the nonlinear forecasting approach (Gómez et al, 2008 ). While cross mutual information values were reported increased in AD (Alonso et al, 2011 ), cross-approximate entropy was observed decreased indicating synchronization better than HC subjects (Gómez et al, 2012 ).…”
Section: Meg Data Analysismentioning
confidence: 99%
“…It has been reported that progressive patients showed a differential profile of FC values compared with those patients who remained stable over time (Bajo et al, 2012 ). Time series was found more predictable for AD by the nonlinear forecasting approach (Gómez et al, 2008 ). While cross mutual information values were reported increased in AD (Alonso et al, 2011 ), cross-approximate entropy was observed decreased indicating synchronization better than HC subjects (Gómez et al, 2012 ).…”
Section: Meg Data Analysismentioning
confidence: 99%
“…Magnetoencephalography is a non-invasive analysis technique used to record the magnetic fields generated by electrical activity in the human brain in a reference free manner (Gomez et al, 2008;Escudero et al, 2009;Jafarpour et al, 2013). The use of magnetoencephalograms (MEGs) to study the background activity of the brain has increased over the years due its advantages, including good temporal resolution, an adequate spatial resolution, particularly when combined with an individual MRI, good signal-to-noise ratio, and relatively robust against volume conduction when compared to other measures such as electroencephalography (Stam et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%
“…The use of magnetoencephalograms (MEGs) to study the background activity of the brain has increased over the years as magnetoencephalography, a non-invasive analysis technique used to record the magnetic fields generated by electrical activity in the human brain [5][6][7], has become more widespread. Large arrays of superconducting quantum interface devices (SQUIDs) immersed in liquid helium at 4.2 K and below, are used to record the weak magnetic fields generated by the brain in a magnetically shielded room to reduce contamination by environmental noise [8][9][10].…”
Section: Introductionmentioning
confidence: 99%